The aesthetics of emptiness the poetry of Jawad Al-Hattab - Dr. Reem Mohammed Tayyib Al-Hafouzi (Journal of College of Education, 2026)
The space, as one of the aesthetic functions as one of the features that can influence the recipient, who will be infatuated with the its aesthetic, cognitive and semantical characteristics. The principle that could form the interactional and responses of all what we sense of material or intangible spaces that were present in Jawad AlHattab’s poems as aesthetic dimensions that were attached with implications that indicate the space including the graffiti space, denotative space, nothingness, death, special space, absence and memory and spectrum and everything that might denote that the space, which requires the recipient to perform an interpretative practice or to block these gaps that need to produce the meaning and the denotation and which, form an aesthetic distance that enriches the white spots or the zero text degree.
Keywords: space, beauty, absence, silence, nothingness.